Theoretical Fundamentals of Cotton Transportation to Pnevmotransport Equipment - D.Turg’unov; O.Sarimsako (International Journal on Human-Computing Studies, 2021)
The article examines the process of mechanical feeding of cotton. Theoretically, the importance of the horizontal feeder in the production process, the influence of the supplier on the quality of the cotton during transportation and labor productivity were applied.